Three‐dimensional pathways of dust over the Sahara during summer 2011 as revealed by new Infrared Atmospheric Sounding Interferometer observations. (6th July 2020) - Cuesta, Juan; Flamant, Cyrille; Gaetani, Marco; Knippertz, Peter; Fink, Andreas H.; Chazette, Patrick; Eremenko, Maxim; Dufour, Gaëlle; Di Biagio, Claudia; Formenti, Paola
Abstract: We present a new characterisation of the three‐dimensional (3D) distribution of dust over the Sahara during summer, exemplified for June 2011. Our approach, called AEROIASI, is based on the innovative retrieval of vertical profiles of the dust extinction coefficient from daily cloud‐free hyperspectral Infrared Atmospheric Sounder Interferometer (IASI) satellite observations. AEROIASI observations clearly agree with other widely used measurements (from lidar and radiometers). The 3D characterisation is focused on the dust maximum in June 2011, located in the central Sahara (17–23°N, 1–7°E) and linked to the major atmospheric dynamical drivers associated with the West African Monsoon (WAM) system. AEROIASI shows the near‐surface dust load to be dominated by five major emission events occurring every 3–4 days. These all occur when the study region is under the influence of northward bursts of the WAM and convection‐related cold pools, likely associated with orographic forcing by the Aïr Mountains. During the earliest (June 10) and the dustiest (June 17) cases, northward advection of moisture over the hotspot is favoured by the superposition of cyclonic circulations related to an extratropical disturbance northwest of the Sahara and to the Saharan heat low over Mauritania, respectively. Convection over the hotspot also triggers wave‐like disturbances that travel westwards. The three dustiest events are characterised by elongated dust fronts moving northwards, with a leading edge spanning 200–300 km horizontally and extending from the surface up to 2 km of altitude. Further south, the dust layer progressively elevates to 3.5 km along the slanted isentropes at the interface of the monsoon and the harmattan, increasingly losing contact with the ground. When northerlies blow over the study region, elevated dust layers at 3–5 km are observed, which are transported southwards within the Saharan air layer and westwards along the northern edge of the African easterly jet (after June 13). Abstract : We present a new characterisation of the three‐dimensional (3D) distribution of dust over the Sahara during summer, using innovative observations of dust vertical profiles derived from hyperspectral satellite measurements of the Infrared Atmospheric Sounder Interferometer. The 3D characterisation is focused on the dust maximum in June, located in the central Sahara and linked to atmospheric dynamical drivers associated with the West African monsoon system. We show the first observational characterisation of the 3D structure of dust plumes associated with convection‐related cold pools.